The Effectiveness of Remedial Instruction on Learning Outcomes in PAI Subject at SD Negeri 7 Paya Bakong - Usman, Usman (The Future of Education Journal, 2025)
This research aims to analyze the effectiveness of remedial programs on student learning outcomes in Islamic Religious Education (PAI) at SD Negeri 7 Paya Bakong. Using a quantitative approach with a quasi-experimental design method, this study involved 30 students who scored below the minimum completion criteria (KKM) as research samples. Data collection was conducted through direct observation, written tests, and documentation. The results showed a significant increase in students' average scores from 65.3 to 78.6 after implementing the remedial program, with 86.7% of students successfully achieving scores above KKM. The implemented remedial program included individual and small group learning, with learning approaches tailored to student needs. Success supporting factors included personal learning methods, school support, and collaboration between teachers and parents. This research recommends developing more innovative remedial learning methods, improving teacher competencies, and strengthening monitoring and evaluation systems to enhance the effectiveness of remedial programs in the future.